2018
DOI: 10.1158/1541-7786.mcr-18-0157
|View full text |Cite
|
Sign up to set email alerts
|

CHP2 Promotes Cell Proliferation in Breast Cancer via Suppression of FOXO3a

Abstract: Calcineurin B homologous protein isoform 2 (CHP2), an essential cofactor for Na/H exchanger isoform 1 (NHE1), is identified to be expressed in various malignant cell lines. However, the clinical significance and biological role of CHP2 in breast cancer remain to be established. Here, CHP2 was markedly overexpressed in breast cancer cells and clinical tumor specimens. Immunohistochemical analysis revealed that the expression of CHP2 was significantly correlated with patients' clinicopathologic characteristics l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…calcineurin homologous protein isoform 2 (CHP2) is expressed in normal intestinal epithelia and also epithelium-like cell line [25], and it might act as a potential role in transmembrane Nat/Ht exchange which can protect cells from serum deprivation induced death [25,26]. The expression of CHP2 has been reported to be significantly increased in human ovarian carcinoma cells [27] and leukemia primary cells [28] and breast cancer cells [29]. Mechanistically, overexpression of CHP2 activated AKT signaling and suppressed the transactivation of the forkhead box O3 (FOXO3/FOXO3a) transcription factor in breast cancer [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…calcineurin homologous protein isoform 2 (CHP2) is expressed in normal intestinal epithelia and also epithelium-like cell line [25], and it might act as a potential role in transmembrane Nat/Ht exchange which can protect cells from serum deprivation induced death [25,26]. The expression of CHP2 has been reported to be significantly increased in human ovarian carcinoma cells [27] and leukemia primary cells [28] and breast cancer cells [29]. Mechanistically, overexpression of CHP2 activated AKT signaling and suppressed the transactivation of the forkhead box O3 (FOXO3/FOXO3a) transcription factor in breast cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CHP2 has been reported to be significantly increased in human ovarian carcinoma cells [27] and leukemia primary cells [28] and breast cancer cells [29]. Mechanistically, overexpression of CHP2 activated AKT signaling and suppressed the transactivation of the forkhead box O3 (FOXO3/FOXO3a) transcription factor in breast cancer [29]. Besides, a study conducted 10-gene signature including CHP2 found that high expression of CHP2 was associated with the recurrence of COAD [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, immunoblotting and RT-PCR techniques have demonstrated that NHE1 and CHP1 are ubiquitously expressed in human tissues while CHP2 is primarily expressed in the intestinal epithelium and in diseased cells including hepatoma, colon AC, cervical carcinoma, and acute leukemia as well as in breast, ovarian carcinoma, and lung cancer. 17,23,24,29 These methods have sampled CHP2 specifically in a limited subset of tissues and cancer types. To comprehensively understand the expression profiles of NHE1, CHP1, and CHP2 expression in non-diseased normal tissues, we analyzed archived RNA-Seq data from the Expression Atlas 31,32 (Figure 1(a)).…”
Section: Expression Profiles Of Nhe1 Chp1 and Chp2 In Normal Tissuesmentioning
confidence: 99%
“…This function likely acts via NHE1-CHP2 interaction to maintain pH i and may involve other signaling pathways like AKT/PKB to control cell proliferation and cell cycle. 29 Because this expression pattern is present in only a subset of cancers, it is likely a driver of tumorigenesis, but not necessary for cancer progression and may provide a general mechanism for increased tumorigenesis and metastasis across cancer types.…”
Section: Nhe1 Chp1 and Chp2 Expression In Lung Cancermentioning
confidence: 99%
“…Breast cancer is the most prevalent malignancies and the leading cause of cancer death among women . According to the statistics of the World Health Organization, about 2.1 million women suffer from breast cancer and an estimated 627 000 women died of breast cancer in 2018 .…”
Section: Introductionmentioning
confidence: 99%